Feminist utopia and dystopia: Marlen Haushofer's Die Wand - Kapelari, Laura (My University, 2014)
Why are we still talking about feminism today? Women now have the vote; they have been given the opportunity to pursue their career while also being a wife and/or mother. Instead of there having been an overhaul of the system, women have been tentatively accepted into the existing patriarchal system, forcing them to play according to its rules and expectations of woman. This realisation serves as the starting point for this research report, which uses the novel “Die Wand”, by postwar Austrian author Marlen Haushofer, to explore the contradictory situation women find themselves in within patriarchal society. In the novel, the female protagonist suddenly finds herself isolated but sheltered from patriarchal structures, as a see-through wall cuts her off from the rest of the world and an apparent nuclear disaster. This initially utopian existence is however soon shattered by the appearance of a male survivor, as he kills the protagonist’s animal companions. Though she shoots him dead, the return of patriarchy, in the form of the unknown man, nevertheless symbolises how woman can never truly free herself from patriarchal binds, and so utopia is seen as turning into dystopia.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, School of Literature, Language and Media: German, 2013